Matematyka

Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska

Wydawnictwo:WSiP

Rok wydania:2015

Wyrażenie -x^2+5x-6 można uzyskać, gdy wykona się działanie 4.0 gwiazdek na podstawie 14 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

Wyrażenie -x^2+5x-6 można uzyskać, gdy wykona się działanie

2
 Zadanie
1
 Zadanie

2
 Zadanie

3
 Zadanie
4
 Zadanie
5
 Zadanie
6
 Zadanie
7
 Zadanie

`A.\ (x+3)(2+x)=x(2+x)+3(2+x)=ul(2x)+x^2+6+ul(3x)=x^2+5x+6` 

`B.\ (x+3)(2-x)=x(2-x)+3(2-x)=ul(2x)-x^2+6-ul(3x)=-x^2-x+6` 

`C.\ (x-3)(2+x)=x(2+x)-3(2+x)=ul(2x)+x^2-6-ul(3x)=x^2-x-6` 

`D.\ (x-3)(2-x)=x(2-x)-3(2-x)=ul(2x)-x^2-6+ul(3x)=-x^2+5x-6` 

 

`odp.\ D`